CASE STUDY OF SPEECH DELAY IN CHILDREN AGED 5 YEARS - Ririn Martuti (Jurnal Scientia, 2023)
This study aims to determine the factors behind speech delay in children aged 5 years. Speech delay is a serious problem and must be treated immediately because it can have a bad impact on children. Speech delay for children can be known from inaccurate articulation or words used by children, causing difficulty in understanding the meaning of their words. Speech delay is when the child's level of speech development is not in accordance with his age or below the average age. This research uses qualitative research methods with a case study approach. The resource persons in this study are the parents of the research subjects. Data collection techniques use observation, interview and documentation techniques. Data analysis techniques use data collection, reduction, display, verificcasion. The results of this study show several factors behind speech delays of children are lack of vocabulary, frequent watching of television, the influence of gadgets, imitated models, lack of interaction and communication stimulation, family history, and low parental education.